Rekonstruksi Argumen Keadilan Berimbang Hak Laki-Laki dan Perempuan dalam Waris Islam - Abdul Jalal, Luqman (Tasyri' : Journal of Islamic Law, 2025)
The concept of Islamic inheritance of two to one between men and women is contradicted by the logic of justice and gender equality. This requires reinterpretation, adjusting its socio-historical context. In this sacred text, there is a goal of substantive justice, because it is related to interactions between fellow human beings and socio-economics. The Principle of Balanced Justice answers this discourse which is considered discriminatory. Namely, providing rights proportionally and in balance with obligations, the obligation of the husband to support his wife and family. Men and women have equal rights to heirs, not related to the issue of gender equality. This study uses a descriptive analysis method, by presenting data from literature studies, books, journals, articles related to the issue of justice in Islamic inheritance law, then drawing conclusions. This study concludes that the concept of Islamic inheritance is the true justice of God Who knows the ins and outs of human nature, based on Balanced Justice between the rights and obligations of men and women. The principle of balanced justice is based on the principle of ijbari, the transfer of ownership of property according to God's provisions and all parties submit. The Principle of Balanced Justice has been regulated in the material law of Islamic Inheritance in Indonesia. The principle of balanced justice is based on substantial justice. And the principle of balanced justice is independent, not contrary to the principle of non-discrimination in PERMA No.3/2017.